Nutrient cycling in off-season cover crops on a Brazilian savanna soil - Boer, Carlo Adriano; Assis, Renato Lara de; Silva, Gilson Pereira; Braz, Antonio Joaquim Braga Pereira; Barroso, Alberto Leão de Lemos; Filho, Alberto Cargnelitti; Pires, Fábio Ribeiro (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the accumulation and the liberation of nutrients (N, P, K, Ca, Mg and S) of cultural residues by three species of cover crops, in off-season. Tested cover crops were amaranthus (Amaranthus cruentus L.), pearl millet (Pennisetum glaucum L.) and finger millet (Eleusine coracana (L.) Gaertn.). The experiment was carried out in a Typic Haplorthox clay texture soil. A randomized block desing in a split-plot array in time, with four replications, was used. At the flowering of the species, the production of dry matter and the accumulation of nutrients were evaluated. Proportional samples of dry matter of each cover crop species were placed in litter bags, which were distributed on the field plots surface, collected and weighed every 30 days, until 240 days after installation of the bags. The largest amounts of accumulated nutrients in the dry matter of the cover crops were observed with the pearl millet and the finger millet. The potassium was the nutrient accumulated in larger amount, reaching 416.9 kg ha-1, in pearl millet. The largest rates of nutrient liberation were observed in the cultural residues of the amaranthus.
Keywords: Amaranthus cruentus; Pennisetum glaucum; Eleusine coracana; decomposition dynamics; nutrient release; no-till